P216 Impact of disease knowledge on quality of life of inflammatory bowel disease patients. (25th January 2019) - Casellas, F; Navarro, E; Herrera-deGuise, C; Robles, V; Borruel, N
Abstract: Background: Inflammatory bowel disease (IBD) impairs patients' quality of life (QoL). Several factors are involved in the impact of QoL, being the most important the activity of the disease. Subjective aspects can also be involved in QoL. One factor that has been scarcely studied is the impact of knowledge of the disease on Qol. Patients who are more knowledgeable could have an easier and more active participation in the management of their disease and on the decision-making process thus improving their QoL. We analysed the relationship between patients' objective and subjective disease knowledge and their QoL. Methods: Prospective observational study in IBD patients (regardless of type, activity, treatment, surgery, etc.). Patients signed an informed consent, and completed different questionnaires: QUECOMIICAT questionnaire for objective knowledge; a visual analogue scale of self-perceived knowledge of IBD for subjective knowledge; IBDQ-9 for QoL measurement. We considered that patients had an objective high-level of knowledge if QUECOMIICAT score was >75 and a low-level of knowledge with a QUECOMIICAT score <25. Results: One hundred and forty-four patients were included (83 UC and 61 Crohn's disease). Sixty-nine per cent were in remission at time of inclusion. IBDQ-9 score did not correlate with the level of objective knowledge of the disease by QUECOMIICAT ( r = 0.1, p = ns), in both UC and Crohn's disease patients. IBDQ-9 was also not statistically different between patients with a high level vs. a low level of knowledge (median IBDQ9 of 69 vs. 68 points, p = ns). When only IBD patients in remission were analysed, correlation between QUECOMIICAT score and QoL was also not significant. Spearman test showed that QoL was inversely correlated with disease activity ( r = −0.6, p < 0.001) and positively correlated with self-perceived knowledge ( r = 0.24, p < 0.01). In the multi-variate analysis we found that having an active disease and being female were the only variables independently associated with a worse QoL ( p < 0.01). Conclusions: Quality of life was not influenced with the objective measure of patients' knowledge of IBD. However, higher subjective self-perceived knowledge was associated with a better QoL.